A Review on Seed Germination Studies of Endemic, Endangered and Threatened Flowering Plants of India - Jadhav, Rushikesh Sanjay; Kambale, Sharad Suresh; Auti, Sanjay Gajanan (Indian Forester, 2025)
This comprehensive review explores methods of seed germination and various aspects related to the germination process for endemic, rare, threatened, and endangered plant species. The review also focuses on different methods of viability testing and includes a discussion on the causes of endemism and rarity. Additionally, it examines the molecular aspects of hormones involved in germination. Moreover, it covers diverse approaches about specific endemic, endangered, and threatened species assessing their physical, chemical, and hormonal treatments, effectiveness for mass propagation and thereby conservation. This review serves as a valuable resource for conservationists and researchers, offering insights and strategies for preserving vital plant species. Furthermore, it highlights the importance of understanding the intricate biological and ecological factors that influence seed germination and plant survival. By addressing seed germination strategies, the review aims to contribute to more effective conservation efforts and promote the sustainable management of biodiversity.